2018
DOI: 10.1001/jama.2018.2444
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Loading Dose of Atorvastatin Prior to Planned Percutaneous Coronary Intervention on Major Adverse Cardiovascular Events in Acute Coronary Syndrome

Abstract: clinicaltrials.gov Identifier: NCT01448642.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
2
8

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 26 publications
0
74
2
8
Order By: Relevance
“…Our 30-day MACE rate following STEMI is much higher compared to reports from the Netherlands (3%), India (5%), and Brazil (10%) [26][27][28]. The in-hospital MACE rate was lower in our study population compared with results of recent studies from China (12%), Canada (9%), and India (8%) [27,29,30].…”
Section: Discussioncontrasting
confidence: 70%
“…Our 30-day MACE rate following STEMI is much higher compared to reports from the Netherlands (3%), India (5%), and Brazil (10%) [26][27][28]. The in-hospital MACE rate was lower in our study population compared with results of recent studies from China (12%), Canada (9%), and India (8%) [27,29,30].…”
Section: Discussioncontrasting
confidence: 70%
“…[1][2][3] Previous small trials and systematic reviews that investigated the effect of loading doses of statins before and after PCI have suggested that there may be a reduction in periprocedural myocardial infarction (MI) and in major adverse cardiovascular events (MACE). [2][3][4][5][6] A well-powered study 7 that addressed the effect of loading doses of statin in patients with acute coronary syndrome (ACS) treated with or without PCI did not show clinical benefit in the overall ACS population but did suggest a positive effect in patients undergoing PCI. It is unknown whether timing of a pre-PCI loading dose of atorvastatin was associated with a beneficial treatment effect.…”
mentioning
confidence: 99%
“…Recently published study, the SECURE-PCI (Statins Evaluation in Coronary Procedures and Revascularization) trial was designed to assess the effect of periprocedural administration of statin in patients with ACS and planned coronary revascularization (13). The investigators sought to test an interesting hypothesis whether high dose atorvastatin before invasive management may reduce adverse cardiac events in ACS.…”
Section: Editorialmentioning
confidence: 99%